Fangs of malice : hypocrisy, sincerity, and acting - Wikander, Matthew H. (Studies in theatre history and culture., 2002)
The idea that actors are hypocrites and fakes and therefore dangerous to society was widespread in the seventeenth and eighteenth centuries. Fangs of Malice examines the equation between the vice of hypocrisy and the craft of acting as it appears in antitheatrical tracts, in popular and high culture, and especially in plays of the period. Rousseau and others argue that actors, expert at seeming other than they are, pose a threat to society; yet dissembling seems also to be an inevitable consequence of human social intercourse.